Comparison of three types of Indian donkey populations based on morphometric characteristics - Rahul Behl; S K Niranjan; Jyotsna Behl; R K Vijh (Journal of Livestock Biodiversity, 2025)
The three populations of Indian donkeys; Spiti donkeys distributed in Spiti and Yangthang regions of Himachal Pradesh, Sindhi donkey found in Barmer, Jaisalmer and Jodhpur districts of Rajsthan and Brown type donkeys found mainly in Kurnool and Anathapur districts of Andhra Pradesh were characterized and compared to ascertain whether any signiicant diﬀerences exist in these three populations of Indian donkeys in the studied morphometric parameters. The results of the F-test showed that these three populations to be signiicantly diﬀerent (P<0.01) from each other, both in male and female animals, at almost all morphometric parameters studied. In pairwise comparison, the Sindhi donkeys showed signiicant diﬀerences from Spiti as well as Brown type donkeys of Andhra Pradesh in most of the studied morphometric parameters both in male and female animals. However, the Brown type donkeys of Andhra Pradesh showed signiicant diﬀerences from Spiti donkeys only in limited number of biometric parameters both in male and female animals.